The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/biom12060833
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin D Receptor Gene Polymorphisms and Periodontal Bacteria: A Clinical Pilot Study

Abstract: Background: Periodontitis is an inflammatory disease caused by microorganisms involving the supporting tissues of the teeth. Gene variants may influence both the composition of the biofilm in the oral cavity and the host response. The objective of the study was to investigate the potential correlations between the disease susceptibility, the presence and the quantity of periodontopathogenic oral bacterial composition and the VDR gene polymorphisms. Methods: Fifty (50) unrelated periodontal patients and forty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Studies on the association between VDR gene polymorphisms and CP mainly focused on BsmI, FokI, ApaI, and TaqI. Some studies have shown a signi cant association between polymorphisms and CP [11,16,26,27,28]. According to a meta-analysis conducted on the Chinese population [29], individuals with the AA+AG genotype of the VDR BsmI polymorphism were found to be more prone to periodontitis in southern China, whereas those with the ApaI TT+TG genotype had a lower risk of developing periodontitis in northern China.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the association between VDR gene polymorphisms and CP mainly focused on BsmI, FokI, ApaI, and TaqI. Some studies have shown a signi cant association between polymorphisms and CP [11,16,26,27,28]. According to a meta-analysis conducted on the Chinese population [29], individuals with the AA+AG genotype of the VDR BsmI polymorphism were found to be more prone to periodontitis in southern China, whereas those with the ApaI TT+TG genotype had a lower risk of developing periodontitis in northern China.…”
Section: Discussionmentioning
confidence: 99%
“…However, this condition is reversible if proper hygiene is restored. 67 Actinobacillus , P. gingivalis , Bacteroides forsythus , and Treponema denticola are among the main pathogenic species of anaerobic bacteria associated with the inflammatory response that leads to gingivitis. Periodontitis forms a periodontal pocket between the tooth and the gingiva that is colonized by anaerobic bacteria.…”
Section: Main Oral Conditions Affected By Oral Microbiota “Imbalance”mentioning
confidence: 99%
“…The micro-organism components of the human microbiota are located on both internal and external surfaces, but most are found in the gastrointestinal tract and in the large intestine, with modern calculations estimating the population size to be 3.8 × 10 13 bacteria [11][12][13].…”
Section: Gut and Oral Microbiotamentioning
confidence: 99%